Historia – rzecz ludzka? Tradycja Norwidowska w wierszach Mieczysława Jastruna z lat 1939–1945 - Dakowicz, Przemysław (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The article is focused on revealing traces of Norwid’s literary tradition hidden in the poetry of Mieczysław Jastrun written between 1939–1945. For the contemporary, twenty-century’s poetwitness of the Second World War the author of Vade-mecum turned out to be the master of historic maturity. Jastrun – willing to recognize Norwid as the forerunner of modernity and as the poet whose output only nowadays may be interpreted and appreciated in suitable way-used Norwid’s pattern of historical and philosophical reflection trying to face by poetry painful experience of Hitler’s occupation. The article tries to answer the question why Jastrun found suitable manner of expressing both individual as well collective experience particularly in Norwid’s literary output.